High IP-10 levels decrease T cell function in HIV-1-infected individuals on ART. Issue 6 (25th August 2014) - Ramirez, L A; Arango, T A; Thompson, E; Naji, M; Tebas, P; Boyer, J D
Abstract : IP-10 can inhibit T cell responses in HIV-1 infected subjects on ART. Abstract: HIV-1-infected subjects, despite control of viral replication with ART, have an altered immune cytokine/chemokine milieu. Changes in systemic cytokines and chemokines can alter immune responses. IP-10, in particular, has been associated with pathogenesis in a number of conditions, and we found that IP-10 is increased in serum in subjects who are HIV-1 infected and on stable ART compared with HIV-1-uninfected individuals. In a series of in vitro studies, we found that PBMCs exposed to IP-10 showed a significant decrease in the number of cells capable of secreting IFN-γ, as well as other cytokines, when stimulated with recall antigens. Furthermore, treatment with IP-10 led to decreased antigen-specific calcium signaling and MAPK38 phosphorylation. Importantly, the cytokines, as well as proliferative responses, could be enhanced with an IP-10 Nab. Our findings suggest that IP-10-modulating drugs may potentially enhance T cell responses to vaccination and HIV-1 in HIV+ subjects on ART.